2010
DOI: 10.1089/end.2009.0680
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of Nonmuscle Invasive Urothelial Carcinoma of the Bladder Using Pirarubicin Endoscopy: A Prospective, Single-Center Preliminary Study

Abstract: THP endoscopy may improve the detection of nonmuscle invasive urothelial carcinoma of the bladder, especially CIS and flat lesions. Results indicate that THP is a promising fluorescent dye for diagnosis and follow-up of nonmuscle invasive bladder carcinoma. Moreover, it is inexpensive, easily available, simple to administer, and is associated with few side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Nevertheless, there are difficulties associated with this diagnostic method. These difficulties can be summarized as follows: i) Relatively high rate of false positives and low specificity (~65%); ii) lack of uniform measurement index for the color and strength of fluorescence; iii) non-specific fluorescence disturbing diagnosis; iv) technical staff may have difficulties with the fluorescence attenuation; and v) reagent configuration process is long and complex (2 h waiting time after injection of reagent) ( 15 ). Thus the development of a convenient, inexpensive, sensitive and safe photosensitizer with high specificity has been the focus of attention among researchers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there are difficulties associated with this diagnostic method. These difficulties can be summarized as follows: i) Relatively high rate of false positives and low specificity (~65%); ii) lack of uniform measurement index for the color and strength of fluorescence; iii) non-specific fluorescence disturbing diagnosis; iv) technical staff may have difficulties with the fluorescence attenuation; and v) reagent configuration process is long and complex (2 h waiting time after injection of reagent) ( 15 ). Thus the development of a convenient, inexpensive, sensitive and safe photosensitizer with high specificity has been the focus of attention among researchers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that bladder tumor tissue after absorbing THP, emit red under fluorescence cystoscopy. Some scholars have speculated that with combining THP and fluorescence cystoscopy, we can improve our chances for early diagnosis of bladder urinary carcinoma ( 15 ). We poured THP 15 min prior to operation and observed tumor cells under fluorescence cystoscopy under white light and all tumor cells emitted orange.…”
Section: Discussionmentioning
confidence: 99%